IST (In-Service Training) Model to Improve English Teachers’ Pedagogical and Professional Competencies in the Computer Science Department of Universities in Indonesia - Fransisca Endang Lestariningsih; John Hope; Suwarsih Madya; Joko Nurkamto (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2018)
The fact that English teachers teaching in a computer science department may not really know detail about information technology (IT) as a subject, as well as its terminologies, brings about difficulties when deciding what kind of teaching materials are appropriate to the student’s learning needs. Another issue is that some computer science teachers do not have an English language teaching background. This can be a drawback for this group of teachers since they do not really know how to teach the language. The following discussion is a needs analysis used as a preliminary study to develop an in-service training (IST) model to improve English teachers’ pedagogical and professional competencies in a computer science department. Pedagogical knowledge, skill, and attitude, and professional competency became the core study since these two were the obvious difficulties faced by the two groups of teachers. This study involved English computer science teachers, the curriculum administrator, and the students in two private universities and one state university in Yogyakarta, Indonesia. Observations, open interviews, and questionnaires were used to gather the data.